2021
DOI: 10.1007/s10551-021-04864-7
|View full text |Cite
|
Sign up to set email alerts
|

Harmful Leader Behaviors: Toward an Increased Understanding of How Different Forms of Unethical Leader Behavior Can Harm Subordinates

Abstract: Research on unethical leadership has predominantly focused on interpersonal and high-intensity forms of harmful leader behavior such as abusive supervision. Other forms of harmful leader behavior such as excessively pressuring subordinates or acting in self-centered ways have received less attention, despite being harmful and potentially occurring more frequently. We propose a model of four types of harmful leader behavior (HLB) varying in intensity (high vs low) and orientation (people/relationships or tasks/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 94 publications
1
19
0
Order By: Relevance
“…Under unethical leadership, however, different forms of unethical leader behaviours can target both followers and organisations. This confirms the view that abusive supervision is highly psychological in nature, encompassing high-intensity hostile behaviours that are directed at people (Almeida et al, 2021). The preceding discussion, however, suggests that unethical leadership need not be highly intense or hostile.…”
Section: Unethical Leadership Vs Abusive Supervisionsupporting
confidence: 73%
See 1 more Smart Citation
“…Under unethical leadership, however, different forms of unethical leader behaviours can target both followers and organisations. This confirms the view that abusive supervision is highly psychological in nature, encompassing high-intensity hostile behaviours that are directed at people (Almeida et al, 2021). The preceding discussion, however, suggests that unethical leadership need not be highly intense or hostile.…”
Section: Unethical Leadership Vs Abusive Supervisionsupporting
confidence: 73%
“…In fact, pseudo-transformational leadership, yet another form of destructive leadership, has the potential to yield positive organisational outcomes (Almeida et al, 2021). In contrast, unethical leadership includes behaviours that are undeniably illegal and, at the same time, violate moral standards, thus, granting no benefit of the doubt to the intentionality of the leader's behaviour.…”
Section: Unethical Leadership Vs Destructive Leadershipmentioning
confidence: 99%
“…Transfer and conversion of knowledge to institutional memory essentially adds to the vibrancy of any organisation (Del Giudice et al , 2015). Previous studies have shown that effective knowledge sharing is positively related to prompt project completion (Ardito et al , 2019; Issac et al , 2021a, 2021b), improved organisational performance (Fait et al , 2019; Pereira and Mohiya, 2021), drastically lower costs of production (Pereira et al , 2021) and increased sales and revenue (Ali et al , 2021; Almeida et al , 2021; Cabrera and Cabrera, 2002). Considering these holistic benefits, organistations have diligently invested in efficient knowledge management systems to optimise the levels of knowledge sharing.…”
Section: Introductionmentioning
confidence: 99%
“…The study makes a significant contribution to the literature on harmful leader behaviors by conceptualizing and operationalizing gaslighting behavior in the workplace. Despite its harmful effects on individuals and organizations, gaslighting has received relatively Gaslighting in the typology of harmful leader behaviors (Almeida et al, 2021).…”
Section: Discussionmentioning
confidence: 99%